Macular blood flow changes in dysthyroid optic neuropathy after high-dose intravenous pulse methylprednisolone (IVMP) - Shu-xian Fan; Jia-qi Liang; Jing Wang; Chong Zhou; Shi-you Zhou; Mei Wang; Peng Zeng (Photodiagnosis and Photodynamic Therapy)
Objective: To investigate the changes in macular vessel density (VD) of the superficial layer of retina (SLR) and deep layer of retina (DLR) in dysthyroid optic neuropathy (DON) after high-dose intravenous pulse methylprednisolone (IVMP). Materials and Methods: Eighteen DON patients (29 eyes) who completed high-dose IVMP and 16 healthy individuals (32 eyes) were enrolled in this study. Optical coherence tomography angiography (OCTA) image analysis and comprehensive ophthalmic examinations were performed, including the SLR macular whole-image VD (SLR-mwiVD) and DLR-mwiVD, best-corrected visual acuity (BCVA), the mean deviation of visual field (VF-MD), pattern standard deviation of visual field (VF-PSD) and the other parameters. Results: The SLR-mwiVD (41.39 ± 4.71 vs. 48.13 ± 3.68, p < 0.001) and DLR-mwiVD (40.77 ± 5.85 vs. 49.14 ± 7.02, p < 0.001) were decreased in DON compared to control eyes. After IVMP, visual function parameters were improved, and SLR-mwiVD (49.41 ± 3.18, p < 0.001) and DLR-mwiVD (50.41 ± 4.04, p < 0.001) were increased in the DON group compared to pretreatment. The increased SLR-mwiVD and DLR-mwiVD were significantly correlated with improvements in BCVA (Log MAR: from 0.62 ± 0.49 to -0.01 ± 0.03, p < 0.001), VF-MD (from – 6.89 ± 2.89 dB to – 1.75 ± 1.29 dB, p < 0.001) and VF-PSD (from 4.38 ± 2.52 dB to 2.32 ± 1.64 dB, p < 0.001). Conclusion: The increase in macular VD was significantly correlated with the improvement in visual function in DON after IVMP. Macular VD changes on OCTA may be a useful indicator for the response in DON after IVMP.